The outcome of the seminal fluid parameter collected via coitus interruptus versus mastubation - Mustafa, Kamarul Bahyah; Zainuddin, Ahmad Murad; Idris, Ghazali; Ramli, Roszaman; Abd. Wahab, Noraziana; Awang, Mokhtar; Omar, Mohd Hashim (Malaysian Medical Associations, 2010)
A one year study was carried out to determine the outcome of the seminal fluid parameters collected via masturbation and coitus interruptus in 151 patients who were undergoing intrauterine insermination (IUI) and patients who came for seminal analysis. There were no statistically significant difference in terms of volume, concentration, progressive motility and normal morphology from specimens collected via coitus interruptus compared to specimens collected via masturbation. Pregnancy outcomes were also comparable.